Sociolect Variation of Banjar Language in Social Interactions of Muara Jawa Village Community, Kutai Kartanegara, East Kalimantan - Rika Istianingrum; Ari Musdolifah; Retnowaty; Sajaratun Hayuni; Hartati Ratna Juita (General English Education, 2026)
Sociolect variation refers to language differences as the social characteristics of speakers within a speech community. The Banjar language serves as the local vernacular of the community in Muara Jawa Village, Kutai Kartanegara Regency, East Kalimantan Province, and is not used uniformly. It shows systematic variation influenced by the social background of its speakers. This study aims to identify and analyze Banjar sociolect variation in everyday social interactions, focusing on three social variables: age, social status, and social background. The study employs a social phenomenology approach as the theoretical lens for interpreting speakers' lived linguistic experiences, combined with a qualitative descriptive method as the research design. Data were collected through participant observation, in-depth interviews, and the engaged participant listening technique involving 15 native Banjar speakers selected through purposive sampling. The findings show that age is the most consistently evidenced source of sociolect variation: intergenerational interactions produce contrastive registers between younger and older speakers, while intra-generational teenage interaction is characterized by peer-exclusive solidarity markers and hyperbolic figurative expressions. Social status variation is reflected in asymmetric address forms and pragmatic strategies within transactional contexts, and social background variation is associated with the occupational register of market traders. These demonstrate that Banjar sociolect variation in this heterogeneous community is systematically shaped by social structure, and the Banjar language continues to function as a marker of ethnic and social identity among its speakers. This study contributes to the documentation of sociolect variation in regional minority languages of Indonesia, particularly within ethnically diverse rural communities.